Children's books in england: five centuries of social life - Darton, F. J. Harvey (The British Library Publishing London : New Castle, DE, 1998)
With literature as his central theme, the author of this history of children's books in England also wove in biography and facts of social and commercial history. This edition has additional biographical notes, a supplementary chapter on the late Victorian and Edwardian eras and 60 illustrations.